An effect of crystal tilt on the determination of ions displacements in perovskite oxides under BF/HAADF-STEM imaging mode. Issue 5 (10th October 2016) - Liu, Y.; Zhu, Y.L.; Tang, Y.L.; Ma, X.L.
Abstract: Abstract : Effects of crystal tilt on the determination of the relative positions of different ion columns in compounds such as ferroelectric PbTiO3 are of critical importance, because the displacements of Ti and O relative to Pb correlate directly to the spontaneous polarization and ferroelectric properties. Here a study about the effects of small-angle crystal tilt on the relative image spots positions of different ions in PbTiO3 was carried out under high angle angular dark-field (HAADF) and bright-field imaging for aberration corrected Scanning Transmission Electron Microscope. The results indicate that crystal tilt affects the relative positions of Pb, Ti, and O greatly, and the effects are proved to depend highly on crystal tilt angle and PTO thickness. HAADF image simulations on PbTiO3, SrTiO3, and SrRuO3 indicate that the difference in atomic number is a main contributor to the relative image spot position change of different ion columns when crystal tilts.